Computational design of anti-CRISPR proteins with improved inhibition potency - Mathony, Jan; Harteveld, Zander; Schmelas, Carolin; Upmeier zu Belzen, Julius; Aschenbrenner, Sabine; Sun, Wei; Hoffmann, Mareike; Stengl, Christina; Scheck, Andreas; Georgeon, Sandrine; Rosset, Stéphane; Wang, Yanli; et al. (Nature chemical biology, 2020)
Anti-CRISPR (Acr) proteins are powerful tools to control CRISPR-Cas technologies. However, the available Acr repertoire is limited to naturally occurring variants. Here, we applied structure-based design on AcrIIC1, a broad-spectrum CRISPR-Cas9 inhibitor, to improve its efficacy on different targets. We first show that inserting exogenous protein domains into a selected AcrIIC1 surface site dramatically enhances inhibition of Neisseria meningitidis (Nme)Cas9. Then, applying structure-guided design to the Cas9-binding surface, we converted AcrIIC1 into AcrIIC1X, a potent inhibitor of the Staphylococcus aureus (Sau)Cas9, an orthologue widely applied for in vivo genome editing. Finally, to demonstrate the utility of AcrIIC1X for genome engineering applications, we implemented a hepatocyte-specific SauCas9 ON-switch by placing AcrIIC1X expression under regulation of microRNA-122. Our work introduces designer Acrs as important biotechnological tools and provides an innovative strategy to safeguard CRISPR technologies.
Gesehen am 14.08.2025